2020
DOI: 10.1111/bcp.14587
|View full text |Cite
|
Sign up to set email alerts
|

Developing and testing a set of quality indicators for pharmacist home visit services: A mixed methods study in Japan

Abstract: Objective: Quality indicators (QIs) are an important mechanism by which health services can be evaluated. We aimed to develop a set of QIs for pharmacist home visit services and assess their measurement properties. Methods: A three-step procedure was applied: (1) Selection of existing contentvalidated QIs from the international literature and the development of QIs based on national guidelines and home healthcare professionals' opinions; (2) Expert panel consensus of a preliminary set of QIs using the RAND/UCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…QIs are a recognized mechanism for improving quality use of medicines if they have been robustly developed and their measurement properties scientifically tested. 55 QIs are measurable elements of practice performance for which there is evidence or consensus that it can be used to assess the quality, and hence change in the quality, of care provided. 56 QIs are usually described with a denominator and a numerator.…”
Section: Implementation Solutions: Quality Indicatorsmentioning
confidence: 99%
“…QIs are a recognized mechanism for improving quality use of medicines if they have been robustly developed and their measurement properties scientifically tested. 55 QIs are measurable elements of practice performance for which there is evidence or consensus that it can be used to assess the quality, and hence change in the quality, of care provided. 56 QIs are usually described with a denominator and a numerator.…”
Section: Implementation Solutions: Quality Indicatorsmentioning
confidence: 99%
“…A previous validation study on QIs for pharmacist home visit services showed that 73% of the QI set (29/40) had room for improvement, indicating that the quality of home healthcare services might be higher than the quality of geriatric primary care. 23 In fact, a previous study reported that home care allows for a deeper relationship with the patient than outpatient care, and as a result, higher quality of care could be provided. 36 Given the transition of older people from primary care to home care, it is important to longitudinally evaluate quality of care for them using both QIs.…”
Section: Discussionmentioning
confidence: 99%
“…All interviews were conducted by NS (a female pharmacist and researcher with training and experience in qualitative research) in Japanese via Zoom following a semistructured interview guide and audio-recorded with notes taken during interviews (see online supplemental appendix 3 ). 23 Interviews were continued until three consecutive interviews provided no additional themes (ie, data saturation). 31 Before ending each interview, interviewees were allowed to provide any further comments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Panellists judged the face and content validity of each QI, using a 9–point scale (ranging from 1 “definitely not appropriate” to 9 “definitely appropriate”) with an opportunity to provide suggestions or modifications via SurveyMonkey™ . This study defined appropriateness as “whether care described in the QIs must be provided in principle” and “whether a high QI score would be interpreted as a high–quality care” [ 33 ]. A QI with a median score of 7–9, without disagreement (i.e.…”
Section: Methodsmentioning
confidence: 99%